(untitled) (Revista de Investigaciones Universidad del Quindío, 2013)
In this paper we prepared zeolite ZSM-5 by hydrothermal synthesis and and subsequently modified through leaching and impregnation with Cu2+. The materials were evaluated in the reaction of oxidative dehydrogenation of propane (DHOP). The leaching were carried out with NaOH solution applied to create mesopores and avoid diffusional problems in the catalyst. The impregnation of the material were carried out with different percentages of cupper (3 and 5%), in order to improve the performance of the materials in the reaction. In catalytic studies found that the combined effect of mesoporsosity and impregnation of cupper howed better performance to low temperatures over its parent material.